Evaluasi Pemanfaatan Data Rekam Medis untuk Sistem Informasi Pemasaran di RS PKU Muhammadiyah Temanggung - Sudarno, Min Adadiyah; Qoriatul Fadhilah, Isnaini (Universitas Nasional Karangturi, 2024)
Electronic medical records become one big data source. Well-managed data can provide information needed in marketing management, especially for private hospitals. PKU Muhammadiyah Temanggung Hospital has implemented electronic medical records starting with the use of billing system in 2014. The data managed includes patient demographics. It is necessary to evaluate the use of these data in terms of man, materials, machine, method, money and markets. The study was descriptive qualitative. The data collection process is carried out by conducting interviews and observations. The marketing information system design process carried out with the IT team. The team uses the waterfall method where system designers complete their concepts by going through a library review process and taking inspiration from various CRM (Customer Relationship Management) models. The results showed that electronic data of medical records has been used as material for marketing information systems. The readiness of man and money makes it easy to build a menu bar of the marketing information system on the dashboard of the management information system. The system is still possible to be developed in terms of materials and machines. The method of data utilization is transforming from manual to digital gradually. This is influenced by the readiness of the next prospective data users to become part of the marketing information system developer by utilizing electronic medical record data. Keywords: menu bar, marketing, data, electronic medical records